The Proportions of 6th Year Khon Kaen University Medical Students with Sufficient Knowledge of Medicolegal Autopsies and Reports - Tawinkan, Korawit; Thanapongtorn, Chinuwat; Chaisena, Chuenkamol; Chatpaitoon, Boonyapohn; Kosuwon, Ploy; Teeramart, Wansadej; Bamrerraj, Saowanan; Boonjaraspinyo, Sirinthip (Srinagarind Medical Journal, 2016)
Background and Objective: According to the Thai laws, physicians have duties to perform medicolegal autopsies and write reports. Therefore, there is a need to evaluate knowledge of the final year medical students in order to improve the forensics curriculum. This study aimed to examine: 1) The proportions of 6th year Khon Kaen University medical students who had sufficient knowledge of medicolegal autopsies and reports; and 2) Factors associated with having knowledge of medicolegal autopsies and reports. Method: Descriptive study at Srinagarind hospital, Faculty of Medicine, Khon Kaen University. Study population: A total of 270 6th year medical Students, Khon Kaen University Tools: Self-administered online questionnaire. Analysis: SPSS v.19 and Epi Info v. 3.5.4 were used to analyze frequency, proportions, percentage, median, interquartile range, 95% confidence interval and analytic statistics. Results: The response rate was 64.5%. The proportions of 6th year Khon Kaen University medical students who had knowledge of both medicolegal autopsies and reports were 20.1% (95% CI:14.4%, 26.8%), only medicolegal autopsies and reports were 52.3%( 95% CI: 44.6%, 59.9%) and 32.8%( 95% CI: 29.5%, 40.3%) respectively. The significant factors associated with having knowledge of medicolegal autopsies and reports were high GPA (p=0.012) and opportunities to do medicolegal autopsies (p =0.046). Conclusion: One-fifth of 6th year medical students had sufficient knowledge in medicolegal autopsies and reports. The significant factors associated with having knowledge of medicolegal autopsies and reports were high GPA and opportunities to do medicolegal autopsies.